Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fnins.2017.00209
|View full text |Cite
|
Sign up to set email alerts
|

Spared Nerve Injury Increases the Expression of Microglia M1 Markers in the Prefrontal Cortex of Rats and Provokes Depression-Like Behaviors

Abstract: Pain and depression are frequently co-existent in clinical practice, yet the underlying mechanisms remain largely to be determined. Microglia activation and subsequent pro-inflammatory responses play a crucial role in the development of neuropathic pain and depression. The process of microglia polarization to the pro-inflammatory M1 or anti-inflammatory M2 phenotypes often occurs during neuroinflammation. However, it remains unclear whether M1/M2 microglia polarization is involved in the neuropathic pain induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 55 publications
2
75
0
1
Order By: Relevance
“… 24 , 25 In the present study, SNI-induced mechanical allodynia and depressive-like behaviors were confirmed by increased withdrawal threshold and immobility time as well as reduced sucrose preference, which suggested that SNI induced the comorbidity of chronic pain and depression. 15 , 16 Previous studies indicate that SNI surgery induced depression-like behaviors in the early days (7 day 16 or 14 days 15 , 26 after surgery). However, the present study found that depression-like behaviors, such as walking distances in OFT, immobility time in FST, and sucrose preference in SPT, began to decrease on day 28 after surgery, but no statistical difference was found.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 In the present study, SNI-induced mechanical allodynia and depressive-like behaviors were confirmed by increased withdrawal threshold and immobility time as well as reduced sucrose preference, which suggested that SNI induced the comorbidity of chronic pain and depression. 15 , 16 Previous studies indicate that SNI surgery induced depression-like behaviors in the early days (7 day 16 or 14 days 15 , 26 after surgery). However, the present study found that depression-like behaviors, such as walking distances in OFT, immobility time in FST, and sucrose preference in SPT, began to decrease on day 28 after surgery, but no statistical difference was found.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Spared nerve injury has been shown to increase M1 microglia in the central nervous system. 41 The fact that inhibition of microglial activity by minocycline reversed SNI-induced mechanical allodynia further supports the hypothesis that CoPP or CORM-2 treatment exerts antiallodynic effects through reductions in M1 microglia.…”
Section: Discussionmentioning
confidence: 54%
“…Piotrowska et al [11] reported that chronic intrathecal administration of maraviroc diminished NP symptoms and nociceptive threshold as well as decreased levels of pro-inflammatory cytokines in Wistar rats post-CCI. Convincing researches have indicated that switching microglial polarization from the pro-inflammatory M1 phenotype to the anti-inflammatory M2 phenotype represents a novel therapeutic strategy for NP [10][11][12][13]. For example, Willemen et al [13] proposed that persistent hyperalgesia in GRK2 (G protein-coupled receptor kinase)-deficient mice was associated with an increased ratio of M1/M2 type markers in spinal cord microglia/macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The microglial polarization toward the pro-inflammatory M1 phenotype often occurs during NP. Convincing evidence has indicated that modulation of inflammation by inhibition of M1 polarization can be a strategy for treatment of NP [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%